The first oases in Eastern Arabia: society and craft technology, in the 3rd millennium BC at Hili, United Arab Emirates - Sophie Méry (Revue d'ethnoécologie)
In the peninsula of Oman, the first agricultural oases appeared in the 3rd millennium and developed, bringing profound economic and social change. In the sphere of craft technology, various developments occurred, particularly in the pyro-technologies. These changes favored the emergence of a society that reached its peak during the last third of the 3rd millennium, at the end of the early Bronze Age. Then it was transformed and declined by 2100 BC. Approximately a century after, a new type of society/culture emerges, the Wadi Suq Culture, but the subsistence economy of which will continue to base on the agricultural oasis system - except in the (or most of the) coastal sites and the stopping places / hunting places -. The analysis proposed here is centered on the example of the oasis of Hili in the Emirate of Abu Dhabi. Hili is the site on which most specialized studies were realized until now, partially published studies which the author of this article led or in which she took part.